BULAK SUMUR FRAMEWORK: OPTIMALISASI KUALITAS AUDIT SYARIAH DI INDONESIA - Sembilan, Bunga Thuba; Haryono, Slamet (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The many problems that occur in sharia audits in Indonesia starting from the problem of human resources, regulations and audit processes make it necessary to take action in order to improve the quality of institutions and finance in Indonesia. Islamic auditing is very important to be able to evaluate the mistakes that occur in Islamic financial institutions. The problems that arise in the Islamic audit try to be solved by researchers by using the Bulak Sumur well through several strategic offers. In conducting this research, the approach used is a qualitative approach with a method of literature study. The research results obtained in overcoming the problem of Islamic auditing in Indonesia, namely by increasing the number of institutions and improving the materials in auditor training, forming a framework and regulation, forming cooperation between academics and practitioners and adopting related rules, materials, etc. from suitable foreign countries applied in Indonesia.Keywords: Bulak Sumur Framework, Sharia Audit.